The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1745-4549.2008.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Refrigerated Storage on Sensory Profile and Physical-Chemical Characteristics of Minimally Pasteurized Orange Juice

Abstract: Minimal pasteurization of orange juice (OJ) consists of using minimum holding time and temperature to ensure partial inactivation of pectin methylesterase (PME). This process produces juice with preserved sensory attributes and has a better acceptance by consumers when compared with commercially pasteurized OJ. Sensory profile and physical‐chemical characteristics of minimally processed OJ was determined, during refrigerated storage, for two OJ blends with different pH values and the same level of PME thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Physicochemical characterisation of each of the samples included in the study is shown in Table 1. The DP did not result in significant variations in the physicochemical parameters after the application of Total soluble solids ranged from 10.1 to 12.5 ºBrix (average 11.7 ºBrix) in FOJ, this average value is close to those reported for other OJ (11.9-12.8 ºBrix) (Del Caro et al, 2004;Tribess et al, 2009). In accordance with Kola et al (2010), DOJ total soluble solids were 11.2 ºBrix, without a significant decrease in relation to FOJ.…”
Section: Physicochemical Characterisationsupporting
confidence: 79%
See 1 more Smart Citation
“…Physicochemical characterisation of each of the samples included in the study is shown in Table 1. The DP did not result in significant variations in the physicochemical parameters after the application of Total soluble solids ranged from 10.1 to 12.5 ºBrix (average 11.7 ºBrix) in FOJ, this average value is close to those reported for other OJ (11.9-12.8 ºBrix) (Del Caro et al, 2004;Tribess et al, 2009). In accordance with Kola et al (2010), DOJ total soluble solids were 11.2 ºBrix, without a significant decrease in relation to FOJ.…”
Section: Physicochemical Characterisationsupporting
confidence: 79%
“…Total soluble solids ranged from 10.1 to 12.5 ºBrix (average 11.7 ºBrix) in FOJ, this average value is close to those reported for other OJ (11.9–12.8 ºBrix) (Del Caro et al ., ; Tribess et al ., ). In accordance with Kola et al .…”
Section: Resultsmentioning
confidence: 97%
“…The physicochemical characteristics of the minimally pasteurized orange juice did not noticeably change with storage under refrigeration (Tribess et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Farnworth et al (2001) reported the same behavior for soluble solids from fresh orange juice when compared with pasteurized orange juice. The physicochemical characteristics of the minimally pasteurized orange juice did not noticeably change with storage under refrigeration (Tribess et al 2009). Figure 1e shows the behavior of the ascorbic acid content of the fresh and pasteurized organic passion fruit pulps during refrigerated storage.…”
Section: Physicochemical Characteristicsmentioning
confidence: 98%